2013
DOI: 10.4132/koreanjpathol.2013.47.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Finding and Characterizing Mammary Analogue Secretory Carcinoma of the Salivary Gland

Abstract: BackgroundA new tumor entity of the salivary glands, mammary analogue secretory carcinoma (MASC) with ETV6-NTRK3 translocation, has recently been proposed. MASC was originally diagnosed as adenocarcinoma, not otherwise specified (ANOS), or acinic cell carcinoma (AciCC) by the current World Health Organization classification. We aimed to identify MASC cases by molecular tests, and to characterize their clinical, histological, and immunohistochemical features.MethodsThirty cases of MASC candidates were selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
119
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(130 citation statements)
references
References 9 publications
11
119
0
Order By: Relevance
“…There have been 11 reported cases in patients under 18 years of age [6,13,26,[29][30][31][32][33][34][35][36]. One of our cases with rearranged ETV6 involved a 12-year-old female making this the youngest reported MASC in literature.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…There have been 11 reported cases in patients under 18 years of age [6,13,26,[29][30][31][32][33][34][35][36]. One of our cases with rearranged ETV6 involved a 12-year-old female making this the youngest reported MASC in literature.…”
mentioning
confidence: 78%
“…However, there was no significant difference between the two groups. Another study reported local recurrence in 3/9 cases after a median time of 44 months (range, 10-101) [31]. Out of the 172 MASC cases reported in the literature until early 2015, only seven patients died from disease.…”
mentioning
confidence: 98%
“…These tumors were termed mammary analogue secretory carcinomas (MASC). Since this initial report, there have been approximately 100 additional cases published [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. These have been previously diagnosed as unusual variants of acinic cell carcinoma, adenoid cystic carcinoma, cystadenocarcinoma, mucoepidermoid carcinoma or adenocarcinoma, NOS.…”
Section: Mammary Analogue Secretory Carcinoma Of the Salivary Glandsmentioning
confidence: 99%
“…The overall mortality is approximately 5 %; tumors that present with a higher stage are usually more aggressive and have a worse prognosis. Four cases have been associated with high-grade transformation [21,29]. These latter tumors are larger than typical MASC, reported up to 8 cm in greatest dimension.…”
Section: Mammary Analogue Secretory Carcinoma Of the Salivary Glandsmentioning
confidence: 99%
“…Microscopically, the tumour is a circumscribed (but not encapsulated) multinodular mass divided by fibrous septa with microcystic, glandular and solid growth patterns. [4,8] Tumour cells are relatively uniform. [11] The tumour can invade within the salivary gland and can extend into the surrounding structures.…”
Section: Discussionmentioning
confidence: 99%